2007
DOI: 10.1175/bams-88-6-913
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Uncertainties and Biases Associated with Surface Temperature Measurement Sites for Climate Change Assessment

Abstract: The use of temperature data from poorly sited stations can lead to a false sense of confidence in the robustness of multidecadal surface air temperature trend assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 39 publications
(64 reference statements)
3
74
0
Order By: Relevance
“…correlation coefficient of adjusted USHCN vs NARR for Orangeburg: 0.93). This agreement confirms findings from previous studies, which show that both NCEP/NCAR and NARR satisfactorily capture the observed intra-seasonal and inter-annual fluctuations (Kalnay and Cai, 2003;Kalnay et al, 2006;Pielke et al, 2007a). Furthermore, the combined use of observations and reanalysis can yield additional information that is related to station environment and observation practices.…”
Section: Observation Reanalysis and Omr Trendssupporting
confidence: 90%
See 2 more Smart Citations
“…correlation coefficient of adjusted USHCN vs NARR for Orangeburg: 0.93). This agreement confirms findings from previous studies, which show that both NCEP/NCAR and NARR satisfactorily capture the observed intra-seasonal and inter-annual fluctuations (Kalnay and Cai, 2003;Kalnay et al, 2006;Pielke et al, 2007a). Furthermore, the combined use of observations and reanalysis can yield additional information that is related to station environment and observation practices.…”
Section: Observation Reanalysis and Omr Trendssupporting
confidence: 90%
“…However, fewer variations occur in the NARR trends (smaller standard deviation: 0.16°C), as compared to the raw observed trends (0.22°C) and, to a lesser extent, the adjusted trends (0.17°C). Such patterns were also observed with the NCEP/NCAR reanalysis (Pielke et al, 2007a), and show that, while station observations express local characteristics, the reanalysis effectively captures regional trends. Previous studies based on the NCEP/NCAR reanalysis have found that the reanalysis exhibits a smaller warming trend as compared to the surface observations (Kalnay and Cai, 2003;Lim et al, 2005;Kalnay et al, 2006) and as a result, the OMR trends (trend differences) are generally positive, especially for urban stations.…”
Section: Observation Reanalysis and Omr Trendssupporting
confidence: 59%
See 1 more Smart Citation
“…As shown in Figure 1, the KMA operates 29 automated weather stations (AWSs) in Seoul today that log air temperature, wind speed and direction, relative humidity, and many other meteorological data at the near-ground level. While several studies report problems with poorly located weather stations for research [75,76], these stations in Seoul are set up mostly on publicly owned land at locations with minimal interference from most immediate surrounding conditions [77].…”
Section: Temperature Datamentioning
confidence: 99%
“…Betts [2006] found that DTR is closely related to the surface net longwave radiation. The use of Tn as a diagnostic global warming metric was also cautioned because it is more sensitive (than Tx) to a variety of factors (e.g., land use change, station siting, and movement of station sites) [Pielke et al, 2007a[Pielke et al, , 2007bFall et al, 2011] and because it reflects a redistribution of heat by changes in atmospheric turbulence rather than by an accumulation of heat in the atmospheric boundary layer [McNider et al, 2012]. These points were clearly illustrated by the widespread timing of daily Tx and Tn occurrences [Wang and Zeng, 2013].…”
Section: Introductionmentioning
confidence: 99%